Why feedback seekers behave proactively? The mediating role of interactional justice - Teng, Huei-Chun; Lin, Cheng-Chen; Peng, Tai-Kuang; Chen, Pei-Fan (Penerbit Universiti Kebangsaan Malaysia, 2020)
Prior research indicates that employees who seek feedback usually have better work performance. But why do feedback seekers behave proactively after receiving feedback information from their supervisors? This question motivates the current research. The purpose of this paper is to explore an important mediator, namely interactional justice, which explains why feedback seekers are motivated to perform proactively. We adopt equity theory to examine whether interactional justice mediates the relationship between feedback seeking behavior and organizational citizenship behavior (OCB) and voice behavior. To test our hypotheses, we conduct two-time-period panel study design and collected data using questionnaires in a Taiwanese electronic goods company. In a sample of 220 employees, the results show that interactional justice is a missing link between feedback seeking behavior and OCB and voice behavior. This study advances the knowledge of creating an environment that allows people to seek feedback freely. Moreover, employers can evaluate employees’ perception of interactional justice regularly via performance appraisal or survey.